Visual-Tactile Experiment for the Elderly With Perceptual Limitations: A Case Study on Neck Massager Design for the Geriatric Population - Yanmin Xue; Shuang Wang; Mengting Xu; Mengcheng Wang; Yang Liu; Kai Qi; Zhi Qiao; Suihuai Yu (IEEE Access)
This study established a subjective-objective combination of emotional demands and an experimental research approach to address the hurdles to smart device use in the elderly caused by deterioration in their perceptual abilities. We used a neck massager as the research object. This product is a regularly used item for the elderly to alleviate neck soreness, but the experience is unsatisfactory in terms of human-computer interfaces, such as button usage. 1) Proposing to analyze product user needs from an emotional perspective, this study designed and implemented visual-tactile perception experiments involving 12 elderly users, including experiments on button shape, button size, button spacing, button material, button texture, and product material. The impact of button specifications and product materials on elderly users’ emotional preferences was objectively investigated by evaluating the $α $ - and $β $ -band power characteristics of the participants’ electroencephalography frontal lobe electrodes (FP1, FP2, F3, F4) and central zone electrodes (FPZ, F ${}_{Z}$ ). 2) Aging-friendly design suggestions for smart products were proposed, and neck massage for the elderly was designed. The findings indicate that the button parameters of round shape, 15 mm diameter, 4.6 mm pitch, and 1 mm depth of concave pattern, as well as the product contact surface material of velvet, are ideal. This study offers a scientific approach to product design and a design reference for aging comparable products in terms of button specifications and material selection.